Self-healing mechanism of deposited carbonates in cement cracks under CO2 storage well conditions - Xing, Xuesong; Zhong, Guangrong; Wu, Zhiqiang; Cai, Jingxuan; Cheng, Xiaowei (Frontiers in Materials, 2022)
In CO2 geological storage wells, the leakage of CO2 along the micro-cracks of the cement sheath of abandoned wells is one of the main risks of CO2 leakage. The chemical reaction between CO2 and oil well cement can realize self-healing of micro-cracks in the cement sheath. In this study, self-healing experiments of artificial cracks in cement-based materials were carried out by simulating the working conditions of high temperature, high pressure and CO2-rich CCS. The formation process and self-healing effect of calcium carbonate (CaCO3) in oil well cement-based materials induced by CO2 under different exposure environments were explored, and the self-healing products were analyzed by X-ray diffraction (XRD) and environmental scanning electron microscopy (ESEM&EDX). X-ray computed tomography (μ-CT) was used to reconstruct the changes of cracks in 3D, and compressive strength, porosity, and permeability were used to evaluate the self-healing properties of cement-based material cracks. The results indicated that for the CS-28(the samples reacted with humid CO2 for 28d) and AS-28(the samples reacted with humid air for 28d) samples, the compressive strength increased by 56.67% and 10.38%, the porosity decreased by 59.37% and 18.19%, and the permeability decreased by 59.91% and 28.07%, respectively. The crack-volume reduction rate of the CS-28 specimen was 57.08%, and the pore-volume reduction rate was 69.20%. Many massive, needle shaped CaCO3 crystals were formed in the pores and cracks of the sample. The reconstruction of the 3D structure of self-healing cement shows that the micro-cracks of the cement are sealed but the pores are increased. The damage prediction based on von Mises stress shows that under the axial force, the healing layer is not prone to damage. This study provides a theoretical and experimental basis for applying self-healing technology in CCS downhole environment, improving the service life of cement sheath and preventing the leakage of stored CO2.